Pengembangan Lembar Kerja Peserta Didik Berbasis Realistic Mathematics Education Untuk Membangun Pemahaman Konsep Matematika - Silvia Dini Nahesa; Victoria Karjiyati; Neza Agusdianita (JURIDIKDAS, 2021)
This study aims to produce Student Worksheets using the Realistic Mathematics Education approach to build understanding of mathematical concepts in grade IV of Elementary School; This study is a Research and Development (R&D) research using a 4-D model. Validation is carried out by material experts, design experts and linguists. The developed were given scores and responses by 4 public elementary school teachers in Bengkulu City. Data analysis techniques used descriptive statistical analysis of the results of expert validation and teacher responses as well as qualitative descriptive analysis of comments from expert validation and teacher responses.. The results of the validity test of the mathematics that have been developed with the results of the material experts are 88.89 with a very valid category, the design expert validation is 94 with the very valid category, the validation of the linguist 90 is very valid and the teacher's response is 87.66 with the very category. valid as the final product of development and limited trial results to get an average value of 83.4 with completeness of 88.89%.